Revision of the Alitta virens species complex (Annelida: Nereididae) from the North Pacific Ocean - Villalobos-Guerrero, Tulio F.; Bakken, Torkild (Zootaxa, 2018)
Alitta virens species complex encompasses elongate nereidids appreciated commercially both in the fishing and aquaculture industries. This complex has been well studied in biological and ecological terms. Nevertheless, detailed taxonomic analyses have scarcely been addressed, to the extent that only a few species in the complex have been recognized as valid but with some difficulties: Alitta brandti Malmgren, 1865 (Sea of Okhotsk), A. grandis (Stimpson, 1853) (northeastern USA) and A. virens (Sars, 1835) (Norway). Whereas, other several species have typically been regarded as synonyms, including those originally described from the North Pacific Ocean: Nereis ( Alitta ) virens plenidentata Moore, 1909 (California, USA), Nereis dyamusi Izuka, 1912 (Japan) and Nereis foliata Baird, 1863 (Vancouver, Canada). In this study, an examination of the immature and epitoke type and non-type material available for the A. virens species complex from the North Pacific was carried out. Herein, the status of A. brandti as a valid species is reinforced being clearly distinct from A. virens and related species. Alitta dyamusi n. comb., A. plenidentata n. comb. and A. williami nom. nov. are reinstated and transferred to Alitta , the specific epithet of the latter species is a replacement name for Nereis foliata Baird, 1863, which is a junior, primary homonym of Nereis foliata Dalyell, 1853. Lectotypes for A. plenidentata n. comb. and A. williami nom. nov. are designated. The North Pacific species of the A. virens complex, excluding A. plenidentata n. comb. which has several distinctive features that differ from all the Alitta species, are characterized by having homogomph spinigers in both supracicular and subacicular neurochaetae, oral ring with a larger number of rows and paragnaths, and epitoke males with unmetamorphosed pygidium and epitoke-modified chaetae in both neuropodial fascicles. The morphology of epitoke females in the A. virens complex is described for the first time. Identification keys to atoke and epitoke species of this complex are also provided. author email: tvillalobos@ecosur.edu.mx
World Polychaeta Database (WPolyDb)